Analysis of retracted publications in the biomedical literature from turkey - Kocyigit, Burhan Fatih; Akyol, Ahmet (Korean Acad Medıcal Scıences)
Background: Retraction is a process for correcting the literature and provides a barrier to the dissemination of publications that include major faults or false-misleading data. The aim of this study was to examine the characteristics of retracted articles in the biomedical field sourced from Turkey. Methods: In this descriptive cross-sectional study, all retracted publications from Turkey on PubMed were listed without date restriction. Data covering the article title, authors, publication date, retraction date, time between publication and retraction dates (in months), journal, article type, country of the corresponding author, peer review timeline (in days), reason for retraction, and subject area of the retracted item were recorded. Citation data were obtained using the Scopus database. The altmetric attention scores of the articles were recorded. Results: A total of 102 articles were listed and after the implementation of exclusion criteria, 86 articles were included for analysis. The first retracted article was published in 2000 (n = 1), while the most retracted articles were published in 2020 (n = 11). The median time lag between publication and retraction was 10.33 (0.73-144.06) months. The main factors causing retraction were plagiarism (n = 23), duplication (n = 22) and error (n = 17). The total number of citations was 695. A total of 224 citations were in the pre-retraction period and 471 citations were in the post-retraction period. Conclusion: The retracted article counts showed a rising trend over the years. The leading causes of retraction for articles from Turkey were plagiarism, duplication, and error. It was found that the articles continued to be cited after the retraction. Researchers in Turkey should be educated on retraction, particularly plagiarism and duplication. Strategies should be developed to prevent articles from being cited after retraction.
Keywords: Retraction; Turkey; Article; Publication; Plagiarism; Duplication; Ethics